In vitro release of metformin hydrochloride from topical vehicles for dermal drug delivery - Tomić, Zorana; Čekić, Tijana; Bubić Pajić, Nataša (Archives of Pharmacy, 2022)
An important role in a number of skin pathologies (e.g. melanoma) of metformin hydrochloride (MET), a commonly used drug for antidiabetic therapy, is recently reported. Due to large dose, low efficiency and systemic side effects, MET oral administration is not considered as appropriate for therapy of such diseases. To achieve the best treatment of skin disorders, drug penetration into deeper skin layers represents an important scientific interest. Since drug release is a prerequisite for drug skin absorption and its therapeutic efficacy, in vitro release study was performed as to select appropriate topical formulations for MET dermal delivery. Two creams (amphiphilic and hydrophilic) and two hydrogels with 30% (w/w) MET and two microemulsions of MET (5%, w/w) were used as vehicles for topical application of MET. The in vitro drug release tests were performed using Franz diffusion cells. The obtained results suggested that MET release was strongly influenced by physicochemical properties and structure of the investigated vehicles. MET detected in the receptor chamber was the highest for hydrogels compared to the other formulations. MET release from both creams was limited and reached up to 8.54 mg/cm2 after 8h. Microemulsions containing a six-fold lower drug concentration released up to 5.37 mg/cm2 of MET, however, a greater proportion of MET reached the receptor phase from microemulsions than from creams. The results of the current study indicated a better in vitro performance of MET hydrogels and microemulsions and they could be developed further through adequate ex vivo and in vivo studies.